Difficult diagnosis and rare morphology of lymphangioleiomyomatosis with giant cysts. (2019) - Welter, Stefan; Thrull, Philipp; Westhoff, Michael; Bach, Peter; Popper, Helmut; Maschek, Hans-Jörg
Abstract: We report on a 32-year-old woman with a second manifestation of a tension pneumothorax two weeks after drainage therapy. The chest CT-scan revealed multiple large bilateral pulmonary cysts. She underwent minimally invasive wedge resection and pleurectomy for treatment. The extensive histologic evaluation revealed the diagnosis of a lymphangioleiomyomatosis (LAM) with an uncommon pattern of lung cysts. Initial staining for HMB-45 was negative. Repeated evaluation of other sections and reference pathology examination detected minimal expression of HMB-45. This case illustrates that immunohistochemistry for HMB-45 may be negative, although LAM is present and repeated immunohistochemistry may be necessary to establish the correct diagnosis.